Body composition and dietary intake of combat sports athletes: a systematic review - Herrero Barceló, J. F.; Martínez Sanz, J. M.; Castillo Martínez, M. (Nutrients, 2026)
Background/Objectives: Combat sports are characterised by successive high-intensity and short-duration episodes (rounds) interspersed with short rest periods (intermittent nature). Athletes` body composition and dietary intake are closely related to physiological demands, and they are determining factors in athletic performance. The aim of this systematic review was to describe the body composition, dietary intake, and food habits of male and female combat sports athletes, and to verify whether they met nutritional recommendations.